ACTIVE ASSISTED MOVEMENT DALAM MENJAGA KEMAMPUAN FUNGSIONAL PADA KONDISI DUCHENNE MUSCULAR DYSTROPHY - Faqih, M Izza Zulfana; Wahyu Tri Sudaryanto,; Salma Muazzaroh, (Journal of Innovation Research and Knowledge, 2023)
Background: Duchenne muscular dystrophy which is a recessive x-linked disorder that often affects males. Duchenne muscular dystrophy is caused by mutations in the dystrophin gene at the Xp21 locus so that dystrophin protein is not produced or dystrophin deficiency and structural abnormalities occur. Dystrophinopathies are X-linked recessive disorders affecting 1 in 5,000 to 1 in 6,000 live male births. The prevalence of DMD is less than 10 cases per 100,000 males. Objective: Physiotherapy management in this case aims to determine the benefits of providing physiotherapy interventions in the form of active assisted and passive movement and stretching in patients with Duchenne muscular dystrophy. Methods: This case report was conducted at PLDPI Surakarta by taking patients with Duchenne muscular dystrophy cases by providing physiotherapy modalities in the form of active assisted and passive movement and stretching for 3 physiotherapy sessions. Furthermore, measurements were taken with the GMFM and XOTR Scale in the first to third physiotherapy. Results: From the physiotherapy management given, it was found that functional ability and muscle strength remained unchanged and did not develop. Conclusion: Physiotherapy management in this case report is proven to be able to maintain functional ability and muscle strength in patients with Duchenne muscular dystrophy.